(untitled) (Medical Forum Monthly, 2024)
Ashphyxial Deaths: A Retrospective Study Conducted at Tertiary Care Hospital of Sindh 2-5 Waheed Ali 2. Pardeep Kumar 3. Abrar-ul-Hasnain 4. Zafar Ali Seenhro Cycloplegic Refraction in Children with Cyclopentolate versus Atropine 6-9 Saba Alkhairy 2. Abdul Rasheed 3. Mazhar-ul-Hassan 4. Farnaz Siddiqui Diagnostic Yield of Ultrasonography in the Evaluation of Abdominal Tuberculosis 10-12 Muhammad Ashraf Kasi Frequency of HBV, HCV and Malaria Infections in Cytopenic Patients Coming for Bone Marrow Aspiration to Bacha Khan Medical College Mardan 13-16 Amjad Ali 2. Imtiaz Ahmad 3. Subhan Uddin 4. Mohammad Amjad 5. Farkhanda Learning Style Preferences of Dental Students, Karachi 17-20 Marium Iqbal 2. Laeequz Zaman Lithium Induced Histological Alteration in Testes of Albino Rats and Their Amelioration with Vitamin E 21-25 Muhammad Rashid Ahmed 2. Muhammad Mazhar Hijazi 3. Bushra Sherwani 4. Hafiz Syed Imran ul Haque 5. Masood Ahmed 6. Muhammad Arif Pattern of Utilization of Dental Services in Public Teaching Hospital of Karachi 26-30 Marium Azfar 2. Nosheen Khawar 3. Adnan Anwar Sukkurwala Screening of Hepatitis B and C Viruses in Patients before Ocular Surgical Procedures 31-34 Farnaz Siddiqui 2. Abdul Rasheed 3. Saba Alkhairy 4. Mazhar-ul-Hassan Effect of Female Education on Family Size, Contraceptive Awareness and its Practice 35-37 Samina Irshad 2. Shahzadi Neelam 3. Shakira Asmat A Study of the Spectrum of Homicide in Rawalakot, AJ&K 38-41 Naseer Ahmed Ch 2. Syed Mudassar Hussain 3. Syed Muhammad Zaffar Bukhari 4. Hamayun Mumtaz Outcome of Surgical and Medical Management of Anal Fissure 42-44 Majeed Ullah Buzdar 2. Irfan Qasirani Frequency of Acute ST Elevation Myocardial Infarction and Various Reasons of Pre-Hospital Delay in Early Morning Hours 45-49 Fahad Ahmed 2. Muhammad Tahir Mohyudin 3. Abubakr Ali Saad 4. Babur Ikram 5. Nisar Ahmed Results of Hemiarthoplasty in Basicervical Fracture Neck of Femur (Gardon Type-III & IV) using Austin Moor Prosthesis and their Assessment in Terms of Charnley Hip Score and Harris Hip Score 50-55Mian Muhammad Azhar Renal Mal-Development – A Devastating Side Effect of Ginsenosides 56-60 Sarah Khalid 2. Humara Gulnaz Estimation of Time Since Injuries (Age of Wound) in Living Medico-Legal Cases of Mansehra 61-64 Iftikhar Ahmad 2. Nighat Seema 3. Muhammad Saleem “Choosing the Best Modality for Undergraduate Clinical Training” A Mixed Method Approach 65-68 Naushaba Sadiq 2. Seyyedha Abbas 3. Ayesha Farooq